Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1155/2012/657805
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer in MHD Dusty Boundary Layer Flow over an Inclined Stretching Sheet with Non-Uniform Heat Source/Sink

Abstract: This paper presents the study of momentum and heat transfer characteristics in a hydromagnetic flow of dusty fluid over an inclined stretching sheet with non-uniform heat source/sink, where the flow is generated due to a linear stretching of the sheet. Using a similarity transformation, the governing equations of the problem are reduced to a coupled third-order nonlinear ordinary differential equations and are solved numerically by Runge-Kutta-Fehlberg fourth-fifth-order method using symbolic software Maple. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 18 publications
(2 reference statements)
2
30
0
1
Order By: Relevance
“…A two-dimensional incompressible viscous fluid flow over a flat plate with a convective boundary condition was described by Aziz [28] and the characteristics of convective heat transfer of a fluid heating the plate's bottom surface was shown. Non-uniform heat generation over a stretching sheet in a two-dimensional MHD laminar boundary layer flow and heat transfer characteristics was explained by Ramesh et al [29].…”
Section: Introductionmentioning
confidence: 98%
“…A two-dimensional incompressible viscous fluid flow over a flat plate with a convective boundary condition was described by Aziz [28] and the characteristics of convective heat transfer of a fluid heating the plate's bottom surface was shown. Non-uniform heat generation over a stretching sheet in a two-dimensional MHD laminar boundary layer flow and heat transfer characteristics was explained by Ramesh et al [29].…”
Section: Introductionmentioning
confidence: 98%
“…Crane [1] has modelled the flow over a linear stretching sheet and solved and got in exponential form. Gireesha et.al [7][8][9] have modelled and discussed about the impact two phase flow over an unsteady stretchable sheet. have analysed the flow dynamics of dusty fluid over an inclined stretchable plane.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the heat generation boosted the velocity field. Ramesh et al investigated the momentum and heat exchange of dusty liquid flow with the inclination of a moving surface and found an interesting outcome—the dusty fluid velocity is enhanced, whereas, the velocity of clean diminishes with the growth of the fluid interaction factor. Ali et al investigated the conjugate aspects of heat‐mass transport in magnetized convected flow over an inclined surface.…”
Section: Introductionmentioning
confidence: 99%